Supercapacitors 2013
DOI: 10.1002/9783527646661.ch7
|View full text |Cite
|
Sign up to set email alerts
|

Li‐Ion‐Based Hybrid Supercapacitors in Organic Medium

Abstract: Environment protection and sustainable energy development have recently become a growing industry, in which energy storage devices are such important components that they play crucial roles. Energy storage devices include batteries, for example, lithium-ion batteries, nickel-metal hydride batteries, and lead-acid batteries, which have high energy densities. The batteries are under vigorous study for further increasing their energy density so that they can power electric vehicles. On the other hand, electric do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 33 publications
1
30
0
Order By: Relevance
“…69 In addition, conducting polymer-based electrochemical capacitors exhibit lower cycle life due to volume change or swelling as a result of the doping (intercalation)/de-doping (de-intercalation) of ions. 67 The conductivity of conducting polymer was rst reported in 1963 by McNeill and co-workers. 65 They exhibit the pseudocapacitive and conductive behavior via electron delocalization in conjugated chemical bond system along the polymer backbone.…”
Section: Pseudocapacitorsmentioning
confidence: 99%
See 4 more Smart Citations
“…69 In addition, conducting polymer-based electrochemical capacitors exhibit lower cycle life due to volume change or swelling as a result of the doping (intercalation)/de-doping (de-intercalation) of ions. 67 The conductivity of conducting polymer was rst reported in 1963 by McNeill and co-workers. 65 They exhibit the pseudocapacitive and conductive behavior via electron delocalization in conjugated chemical bond system along the polymer backbone.…”
Section: Pseudocapacitorsmentioning
confidence: 99%
“…It is suggested that the adsorption-desorption of anions from electrolytes occurs on the AC electrode while lithium intercalation-deintercalation occurs in the graphite electrode. 67 Similarly, Sivakkumar and Pandolfo have fabricated a lithium-ion capacitor assembled with pre-lithiated graphite anode and AC cathode, exhibiting energy density of 100 Wh/kg. 125 However, the study reveals that the instability of pre-doped graphite during the cycling is the main root cause of the capacity deterioration.…”
Section: Ternary Compositesmentioning
confidence: 99%
See 3 more Smart Citations